The acquisition of Greek gender by bilingual children: The effects of lexical knowledge, oral input, literacy and bi/monolingual schooling. (October 2019) - Prentza, Alexandra; Kaltsa, Maria; Tsimpli, Ianthi Maria; Papadopoulou, Despina
Aim: The objectives of this study are to examine (a) the development of gender assignment and agreement in real and pseudo nouns by bilingual Greek-Albanian children and (b) how different input-related factors impact on these different processes. Methodology: Real and pseudo nouns were investigated to assess the effect of lexical knowledge (real nouns) and of morphological cues (pseudo nouns). Four tasks eliciting gender production in determiner phrases (assignment) and adjective predicates (agreement) for real and pseudo items were administered. Data: 150 bilingual children and 57 Greek monolingual children, aged 8–12 years old, were tested. Bilingual performance is investigated in relation to the role of the bilinguals' Greek vocabulary knowledge, as well as in relation to early/current language exposure, oral input, literacy, monolingual/bilingual schooling and parental education as a proxy for socioeconomic status. Findings: The results show a strong relationship between the bilinguals' performance and their Greek vocabulary development, the amount of oral Greek input and the type of school they are attending. For real nouns, oral Greek input is a positive predictor for accuracy, while literacy in Albanian is associated with lower scores. In pseudo nouns, bilinguals attending bilingual schools are shown to perform significantly better than those attending monolingual schools. Originality: The contribution of this study is related to (a) the examination of pseudo nouns along with real ones showing that gender marking in the former involves a distinct process, (b) the finding regarding the pervasive role of vocabulary knowledge and (c) the consideration of schooling type in relation to the development of a specific grammatical feature. Implications: Bilingual education was shown to positively affect the development of gender, which suggests that schooling type has a significant impact not only on literacy development but also on grammatical development.